Estimating the biodegradation of PHB/PBAT films – An experimental design approach - Fernandes, Miguel; Salvador, Andreia F.; Madalena, Daniel A.; Vicente, António A. (Polymer degradation and stability, 2025)
•The most important factor was the temperature.•Higher temperatures (45 ≥ 37 ⁰C) improved biodegradation in soil.•The addition of nitrogen had no impact on the biodegradation.•A MHC of 60% produced similar results to the range recommended by the standards.•The CCRD was used to modulate the biodegradation of bioplastics using fewer trials. The massive use of plastics in various applications, particularly packaging, generates enormous amounts of plastic waste that can be found almost everywhere, including in soil. This represents a serious environmental pollution issue since the biodegradability in soils can take several years, depending on the microbial composition, the physical and chemical characteristics of plastics, and other relevant environmental factors such as the soil temperature, the soil moisture holding capacity (MHC), and the carbon:nitrogen (C/N) ratio. In this work, we evaluated the importance of these soil physical-chemical parameters on the biodegradation of a plastic film composed of PHB/PBAT. A design-of-experiments methodology, namely the Central Composite Rotational Design (CCRD) was used to determine the effects of these parameters in the biodegradation of the films in soil. The carbon dioxide evolution was followed for 6 months following the guidelines of the ASTM D5988 (2018). The results showed that the most important factor was the temperature. Higher temperatures (≥ 37 °C) accelerated biodegradation while the adding of nitrogen (aqueous solution of ammonium chloride) had no impact on this process, probably because the C/N ratio pre-existing in the soil was suitable to guarantee microbial activity. Although a MHC between 80% and 100% is recommended by international standards, 60% MHC produced similar results. According to the methodology, the best combination possible includes a temperature of 37 °C and a MHC ranging from 60 to 100%.